Temporary colocation and collaborative discovery: Who confers at conferences - Chai, Sen; Freeman, Richard B. (Strategic Management Journal, 2019)
Research Summary The flow of knowledge is closely linked to proximity. While extensive works show that long‐term geographic proximity affects work behavior, little is known about the effect of short‐term colocation, such as conferences. Using participant data at Gordon Research Conferences, we estimate difference‐in‐differences and instrumental variable models, which show that attendees who have no prior within‐conference collaborations are more likely to collaborate with other attendees, and that the researchers who have worked previously with other attendees are more likely to continue their collaborations. We also find that researchers who are junior, are located closer to the conference venue, and have established prior ties to the conference draw more collaborative benefits from temporary colocation across organizations. Thus, going to a conference alters the creation of collaborations. Managerial Summary Managers face important decisions with long‐term strategic ramifications regarding where to locate offices, plants, and R&D centers, as well as how to lay out workspaces inside the firm to enhance knowledge spillover and collaboration. Permanent proximity, however, may be difficult and sometimes impossible to attain. One potential way of overcoming the distance disadvantage in knowledge spillover and tie formation is through temporary colocation events that bring together individuals from distant locations in an environment of temporary proximity. We find that individuals who attend temporary colocation events across organizational boundaries are more likely to collaborate with one another subsequently. Hence, managers of firms should pledge substantial funds for employees to participate in these events so as to impact the subsequent direction of R&D activities.